Some observations on the biology of Nemipterus mesoprion (Bleeker) from Veraval (Gujarat) - Raje, Sadashiv Gopal (Indian Journal of Fisheries, 2011)
The length-weight relationship in Nemipterus mesoprion is calculated to be log W= -10.7134 + 2.9124 log L. The Kn values were calculated separately for males and females in relation to months and size groups. Females attain 50% maturitj' at 134 mm. This species appears to spawn from September to March. The fecundity estimates range from 5,344 to 64,369 ova in the size range 104-198 mm. The males dominated the commercial catch and the male to female ratio was 2.57:1. Empty stomachs occurred in high percentage in both males and females. This species is a demersal carnivore feeding on crustaceans, fishes, molluscs and annelids in the order of preference.